Antibiotic prophylaxis for the prevention of respiratory tract infections in antibody deficient patients: A retrospective cohort study - Grammatikos, Alexandros; Albur, Mahableshwar; Gompels, Mark; Barnaby, Catherine Louise; Allan, Susan; Johnston, Sarah (Clinical infection in practice, 2020)
•Antibiotic prophylaxis seems to be beneficial in antibody deficient patients.•The emergence of antimicrobial resistance did not seem to affect patient outcomes.•The choice of the antibiotic regiment should be individualised.•Prophylaxis can be either first-line or an add-on to immunoglobulin therapy. Antibiotic prophylaxis is commonly used in the management of antibody deficient patients, but very few studies have attempted to define its role in this particular patient population. The aim of this study was to clarify the role of antibiotic prophylaxis in the prevention of lower respiratory tract infections in these patients. In a tertiary Immunology referral centre in England we retrospectively analysed the Immunology database to identify adult antibody deficient patients who had received antibiotic prophylaxis to prevent lower respiratory tract infections over the past 15 years. One hundred and five patients were identified and antibiotic prophylaxis was found to be beneficial in this cohort. There was a significant reduction in the number of positive sputum cultures from 1.61 to 1.05 per patient year. Infection-related hospital admissions also dropped significantly, from 0.53 to 0.19 per patient year. Similar results were seen in the subgroup of patients that were not receiving immunoglobulin replacement. Although our study showed emergence of secondary antimicrobial resistance (14%) and a 7.5% rate of colonisation with multi-drug resistant organisms, these factors did not have any significant impact on outcomes. The above findings suggest that antibiotic prophylaxis should be considered in antibody deficient patients who are troubled by recurrent lower respiratory tract infections. Randomized controlled trials are required to confirm these findings.